Performance of the CLEO IIILiF-TEA ring imaging Cherenkov detector in a high-energy muon beam - Artuso, M; Ayad, R; Azfar, F; Efimov, A; Kopp, S; Mountain, R; Majumder, G; Schuh, S; Skwarnicki, T; Stone, S; Viehhauser, G; Wang, J; et al. (Elsevier, 2000)
The CLEO III Ring Imaging Cherenkov detector uses LiF radiators to generate Cherenkov photons which are then detected by proportional wire chambers using a mixture of CH4 and TEA gases. The first two photon detector modules which were constructed, were taken to the Fermilab and tested in a beam dump that provided high-momentum muons. We report on results using both plane and 'sawtooth'-shaped radiators. Specifically, we discuss the number of photoelectrons observed per ring and the angular resolution. The particle separation ability is shown to be sufficient for the physics of CLEO III.